Arsenic contamination and potential health risk to primary school children through drinking water sources. Issue 2 (7th February 2023) - Ahmed, Jamil; Wong, Li Ping; Channa, Najeebullah; Ahmed, Waqas; Chua, Yan Piaw; Shaikh, Muhammad Zakir
Abstract: Arsenic exposure through drinking water is a serious public health concern in the southern province of Pakistan. Little information on As exposure to children at school settings is available in Pakistan. The current study aimed to assess arsenic contamination through drinking water sources and estimate its health risk to the children, the potentially malnourished Pakistan population. We used risk assessment models to estimate the hazard quotient index and lifetime cancer risk. Spatial data analysis methods were used to investigate the spatial pattern of As contamination and its relationship with the area's hydrogeology. Across the 423 sampled schools, the drinking water exceeded the WHO permissible limits (19.6% for arsenic and 15% for iron). The arsenic's average incremental lifetime cancer risk (ILCR) exceeded the USEPA permissible limit. The arsenic hotspots were mainly located in the central districts. The present study's findings elaborate that the reduction is the controlling phenomenon in the lower Indus basin in the active flood plains, which is the primary source of fresh groundwater in Sindh and pH-induced dissolution is the second phenomenon observed only in the irrigated area, especially at the boundary of the hotspots. These findings are helpful to inform policymakers on measures to ensure prior treatment of As in the drinking water for the schools in areas adjacent to the riverbank.